2014
DOI: 10.1108/rsr-10-2012-0067
|View full text |Cite
|
Sign up to set email alerts
|

Text a librarian: a look from the user perspective

Lili Luo

Abstract: Purpose – The aim of this paper is to provide an in-depth examination of the use and non-use of text reference service among library users, seeking to evaluate the service from library users' perspective and hence enhance the professional understanding of the best practices of text reference service. Design/methodology/approach – A survey study was conducted among library users, examining user demographics, user's texting behavior, user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For instance, a study conducted by Song and Lee (2012) of international students enrolled at the College of Business at the University of Illinois found that the high total cost of ownership (costs for handsets and monthly data plans) was the main reason 39% of the respondents did not own a tablet computer. A study conducted by Luo (2014) at San Jose State University revealed that some of the respondents to the study did not access the SMS library service because they did not have a texting plan on their mobile phone contracts. Although cost has been identified as a factor in access to library services through mobile phones, trends of mobile phone usage as seen in studies by Lo et al (2016) and Vassilakaki, Moniarou-Papaconstantinou and Garoufallou (2016) show that students still used their mobile phones to access social media and to communicate with their friends and relations using emails, SMS and chats.…”
Section: Factors Impacting Usage Of Mobile Phones To Access Library Smentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a study conducted by Song and Lee (2012) of international students enrolled at the College of Business at the University of Illinois found that the high total cost of ownership (costs for handsets and monthly data plans) was the main reason 39% of the respondents did not own a tablet computer. A study conducted by Luo (2014) at San Jose State University revealed that some of the respondents to the study did not access the SMS library service because they did not have a texting plan on their mobile phone contracts. Although cost has been identified as a factor in access to library services through mobile phones, trends of mobile phone usage as seen in studies by Lo et al (2016) and Vassilakaki, Moniarou-Papaconstantinou and Garoufallou (2016) show that students still used their mobile phones to access social media and to communicate with their friends and relations using emails, SMS and chats.…”
Section: Factors Impacting Usage Of Mobile Phones To Access Library Smentioning
confidence: 99%
“…University libraries in various parts of the world are taking advantage of the proliferation of mobile phones among students , Kumar 2014) coupled with the tremendous computing power they possess (Hossain & Ahmed 2016) to offer services to their clients (Bomhold 2014, Luo 2014. Mobile phones are used to deliver user services (book renewals; e-book and e-journal access), reference services (user queries and instructional services), informational services (notifications), and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…University libraries are increasingly offering their services through a number of mobile phone applications (Luo, 2014) and also creating webpages that are accessed through mobile phones (Bridges et al, 2010;Wilson and McCarthy, 2010). In the context of Malawi, no studies on the use of mobile phone to provide library and information services are available.…”
Section: Introductionmentioning
confidence: 99%
“…Personal and contextual factor could influence a user's decision to use help (Fisher 1983). Librarians have undertaken various studies to evaluate the effective of digital reference services (Pellegrino 2012;Luo 2014). While these studies are useful to libraries looking for best practices in designing online help, they focus on the behaviors of students and effectiveness of existing systems, versus examining how the behaviors of students are reflected in users' preferences in online library help systems.…”
Section: Related Workmentioning
confidence: 99%